Import of community-associated, methicillin-resistant Staphylococcus aureus to Europe through skin and soft-tissue infection in intercontinental travellers, 2011–2016. (June 2019) - Nurjadi, D.; Fleck, R.; Lindner, A.; Schäfer, J.; Gertler, M.; Mueller, A.; Lagler, H.; Van Genderen, P.J.J.; Caumes, E.; Boutin, S.; Kuenzli, E.; Gascon, J.; et al.
Abstract: Objectives: Recently, following import by travel and migration, epidemic community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has caused nosocomial outbreaks in Europe, sometimes with a fatal outcome. We describe clinico-epidemiological characteristics of CA-MRSA detected by the European Network for the Surveillance of imported S. aureus (www.staphtrav.eu ) from May 2011 to November 2016. Methods: Sentinel surveillance at 13 travel clinics enrolling patients with travel-associated skin and soft-tissue infection (SSTI) and analysing lesion and nose swabs at one central laboratory. Results: A total of 564 independent case-patients with SSTI were enrolled and had 374 (67%) S. aureus -positive lesions, of which 14% (51/374) were MRSA. The majority of CA-MRSA isolates from SSTI were Panton–Valentine leucocidin (PVL) -positive (43/51, 84%). The risk of methicillin-resistance in imported S. aureus varied by travel region (p <0.001) and was highest in Latin America (16/57, 28%, 95% CI 17.0–41.5) and lowest in Sub-Saharan Africa (4/121, 3%, 95% CI 0.9–8.3). Major epidemic clones (USA300 / USA300 Latin-American Variant, Bengal Bay, South Pacific) accounted for more than one-third (19/51, 37%) of CA-MRSA imports. CA-MRSA SSTI in returnees was complicated (31/51 multiple lesions, 61%; 22/50 recurrences, 44%), led to health-care contact (22/51 surgical drainage, 43%; 7/50 hospitalization, 14%), was transmissible (13/47 reported similar SSTI in non-travelling contacts, 28%), and associated with S. aureus nasal colonization (28 of 51 CA-MRSA cases, 55%; 24 of 28 colonized with identical spa -type in nose and lesion, 85%). Conclusions: Travel-associated CA-MRSA SSTI is a transmissible condition that leads to medical consultations and colonization of the infected host.